KOMPETENSI SDM DAN PENGARUHNYA TERHADAP KINERJA UMKM BATIK DI KABUPATEN BANYUMAS - Sulistyandari Sulistyandari; Ekaningtyas Widiastuti; Sri Martini (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2016)
The role of SMEs in Indonesia in supporting the economy in Indonesia is quite significant. In the post-1997 crisis in Indonesia, SMEs can prove that this sector could become the foundation for the national economy. Number of SMEs also continued to increase from year to year. SMEs in developing countries is almost always the biggest economic activity in number and ability to absorb labor. Development of SMEs as one of supporting economic growth must be accompanied by the development of human resources in various aspects. HR competency development of SMEs important in order to create a quality workforce to reach corporate goals. The current study focused on SMEs Batik in Banyumas, was to examine the impact of human resource competencies (Knowledge, Skills and Abilities) on company’s performance in SME Batik Banyumas. Research conducted on 65 respondents in Banyumas showed that HR competencies affect the performance of SMEs. Skills have significant effect on the performance of SMEs. However, knowledge and abilities does not effect the performance of SMEs. The owners of SMEs Batik should pay attention to the importance of human resource competencies to improve their performance. It is also important to improve their skills through training and workshops related to batik. Owners of batik needs to involve employees in their knowledge and skills in the production process of batik that can help increase employee and company performance in the future.